2015
DOI: 10.1001/jamapediatrics.2015.1736
|View full text |Cite
|
Sign up to set email alerts
|

Independent Evaluation of Middle School–Based Drug Prevention Curricula

Abstract: IMPORTANCE Lack of robust program evaluation has hindered the effectiveness of school-based drug abuse prevention curricula overall. Independently evaluated randomized controlled trials (RCTs) of universal, middle school-based drug abuse prevention curricula are the most useful indicators of whether such programs are effective or ineffective. OBJECTIVE To conduct a systematic review identifying independently evaluated RCTs of universal, middle school-based drug abuse prevention curricula; extract data on stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…Despite decades of alcohol and drug use awareness campaigns that often take place as early as middle school [24], these findings reflect a nearly two-fold increase over the past 25 years in the proportion of students who are unaware of whether or not their institution has an alcohol and drug policy [7]. In addition to re-examining, redesigning, and enforcing tighter boundaries pertaining to the use of alcohol and drugs among medical students, medical schools may want to prioritize students’ mental and physical health by creating a safe environment to talk about substance use and its consequences without the fear of backlash, and to both provide and promote services and resources for students in need of help.…”
Section: Discussionmentioning
confidence: 99%
“…Despite decades of alcohol and drug use awareness campaigns that often take place as early as middle school [24], these findings reflect a nearly two-fold increase over the past 25 years in the proportion of students who are unaware of whether or not their institution has an alcohol and drug policy [7]. In addition to re-examining, redesigning, and enforcing tighter boundaries pertaining to the use of alcohol and drugs among medical students, medical schools may want to prioritize students’ mental and physical health by creating a safe environment to talk about substance use and its consequences without the fear of backlash, and to both provide and promote services and resources for students in need of help.…”
Section: Discussionmentioning
confidence: 99%
“…For example, iatrogenic effects that were found in early instantiations of the D.A.R.E. program (Flynn, Falco, & Hocini, 2015;West & O'Neal, 2004) nutrition intervention is co-dependent on family microsystems to produce effects. The key in this example is that the intervention priorities are defined by and located within the school but depend on family inputs to produce effects in and beyond the school.…”
Section: Social Interface Model 16mentioning
confidence: 99%
“…The evaluations of the health interventions at school have been carried out and involve specific topics such as prevention of depression and anxiety 6 , the offering of physical activities to students 7 and drug prevention among schoolchildren 8 . No studies have been found that synthesize comprehensively the evaluation of health interventions in school in the world and its different themes.…”
Section: Introductionmentioning
confidence: 99%